Variations of Renal Artery - A Multi-Detector Computed Tomography Study - Anurag; Vishnu Gupta (Academia Anatomica International, 2019)
Introduction:The anatomical knowledge of renal artery variations is gaining importance due to increased incidence of kidney transplantation and related surgical procedures. Normally a single renal artery supplies each kidney. Accessory renal arteries are the commonly seen renovascular variations. So a thorough knowledge of renal arteries is helpful for the smooth conduct and interpretation of interventional radiological procedures and to avoid unexpected complications during surgery. Subjects and Methods:In our study we decided to find out the incidence of accessory renal arteryand also there length and diameter.Results:We studied 60 patients who came for abdominal CT angiography. In CT angiography out of 60 cases 21 cases (35%) had renal artery variation, out of 21 cases 3 cases had bilateral renal artery variations and 2 cases had double accessory renal artery.Conclusion:Knowledge on renal artery variations are necessary during renal transplantation, urological procedures and for radiological interventions.